2015
DOI: 10.1128/iai.01713-14
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule, Odanacatib, Inhibits Inflammation and Bone Loss Caused by Endodontic Disease

Abstract: dPeriapical disease, an inflammatory disease mainly caused by dental caries, is one of the most prevalent infectious diseases of humans, affecting both children and adults. The infection travels through the root, leading to inflammation, bone destruction, and severe pain for the patient. Therefore, the development of a new class of anti-periapical disease therapies is necessary and critical for treatment and prevention. A small molecule, odanacatib (ODN), which is a cathepsin K (Ctsk) inhibitor, was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…Our present findings demonstrate that DCs infiltrate extensively in the periodontitis lesion area, and that PH exacerbates this. Previous studies have shown that activation of OCs (resulting bone resorption) is the essential phenotypic determinant downstream of inflammation in bone tissue . Our results show that the PH increases the severity of OCs infiltration during periodontitis, causing significantly more bone loss than normotensive conditions.…”
Section: Discussionmentioning
confidence: 49%
“…Our present findings demonstrate that DCs infiltrate extensively in the periodontitis lesion area, and that PH exacerbates this. Previous studies have shown that activation of OCs (resulting bone resorption) is the essential phenotypic determinant downstream of inflammation in bone tissue . Our results show that the PH increases the severity of OCs infiltration during periodontitis, causing significantly more bone loss than normotensive conditions.…”
Section: Discussionmentioning
confidence: 49%
“…Similar to the effects of melatonin in this study, previous research reported that the cathepsin K inhibitor odanacatib and NC‐2300 decreased the number of osteoclasts in periapical lesions (Hao et al . , Suzuki et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…), which was reported to play important function in immune cells (Hao et al. ). Additional studies are needed to distinguish between these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…, Hao et al. ). H&E (Haematoxylin and eosin) staining and TRAP (Tartrate‐resistant acid phosphatase) staining were performed by standard methods.…”
Section: Methodsmentioning
confidence: 99%